Statement complementing the EFSA Scientific Opinion on application (EFSA‐GMO‐NL‐2015‐126) for authorisation of food and feed containing, consisting of and produced from genetically modified soybean MON 87705 × MON 87708 × MON 89788 - SEFSA Panel, Genetically Modified Organisms (GMO); Casacuberta, Josep; Barro, Francisco; Braeuning, Albert; Cubas, Pilar; de Maagd, Ruud; Epstein, Michelle M.; Frenzel, Thomas; Gallois, Jean‐Luc; Koning, Frits; Messéan, Antoine; Moreno, F. Javier; et al. (EFSA, 2024)
Following a request from the European Commission, the GMO Panel assessed additional information related to the application for authorisation of food and feed containing, consisting of and produced from genetically modified soybean MON × MON 87708 × MON 89788 (EFSA-GMO-NL-2015-126). The applicant conducted a 90-day feeding study on GM soybean MON 87705 and provided a proposal for post-market monitoring considering the altered fatty acid profile of GM soybean MON 87705 × MON 87708 × MON 89788, to fulfil the deficiencies identified by EFSA GMO Panel, addressing elements that remained inconclusive from a previous EFSA scientific opinion issued in 2020. The GMO Panel concludes that the 90-day feeding study on GM soybean MON 87705 is in line with the requirements of Regulation (EU) No 503/2013 and that no treatment-related adverse effects were observed in rats after feeding diets containing soybean MON 87705 meals at 30% or 15% for 90 days. The GMO Panel reiterates the recommendation for a PMM for food in accordance with Regulation (EC) No 1829/2003 and Regulation (EU) No 503/2013 and concludes that the proposal provided by the applicant is in line with the recommendations described for the PMM plan of soybean MON 87705 × MON 87708 × MON 89788 in the adopted scientific opinion. Taking into account the previous assessment and the new information, the GMO Panel concludes that soybean MON 87705 × MON 87708 × MON 89788, as assessed in the scientific opinion on application EFSA-GMO-NL-2015-126 and in the supplementary toxicity study, is as safe as its non-GM comparator and the non-GM reference varieties tested and does not represent a nutritional concern in humans and animals, within the scope of this application.
Keywords: 90-day feeding study; GMO; MON 87705; MON 87705×MON 87708×MON 89788; post-market monitoring (PMM); soybean (Glycine max)